Measles hepatitis in a vaccinated liver transplant recipient: case report and review of literature. Issue 6 (20th April 2017) - Mohiuddin, Syed Adnan; AlMaslamani, Muna; Hashim, Samar; Panthalayinitharayil, Hanfa Karim; Alkaabi, Saad Rashid; Abdulwahab, Abdulwahab; Derbala, Moutaz
Key Clinical Message: Measles infection, postliver transplant, may lead to a fatal graft loss. Individuals who have been previously exposed to the measles antigen may have a modified disease presentation. Although vaccination may not provide solid immunity, it ameliorates the severity of the disease. Abstract : Measles infection, postliver transplant, may lead to a fatal graft loss. Individuals who have been previously exposed to the measles antigen may have a modified disease presentation. Although vaccination may not provide solid immunity, it ameliorates the severity of the disease.